Pengaruh Family Support terhadap Work Life Balance pada Perawat di Rumah Sakit X - Ayunda Zhillan Afsari; Suhana (UNISBA Press, 2023)
Abstract. Family Support is social support provided by the family in the form of the attitude of family members in giving real assistance and a form of attention to individuals. Work Life Balance is an individual's effort to balance the fulfillment of his roles' needs in work life and personal life. The support given by the family becomes a key resource for an employee to work (King, Mattimore, King, and Adams, 1995). This study aims to determine the picture and effect of Family Support on Work Life Balance in Nurses in Hospital X. The hypothesis of this study is that Family Support influences Work-Life Balance in nurses in Hospital X. Subjects of this study were 55 nurses in the same hospital. The Family Support measuring instrument used in this study is the Family Support Inventory for Workers by King et al. (1995) and the Work-Life Balance measuring instrument based on Fisher's theory. All of the compiled information was analyzed by using multiple regression. The results indicated that 94.5% of nurses had high Family Support and 96.4% of nurses had high Work-Life Balance. Simultaneously, Family Support had a 50.6% impact on their Work-Life Balance. The Family Support aspect that had the most influence on Work-Life Balance was the Instrumental assistance aspect with an influence of 25.71%, while the aspect that had the lowest influence was Emotional Sustenance with an influence of 24.89%. Abstrak. Family Support merupakan dukungan sosial yang diberikan oleh keluarga berupa sikap anggota keluarga dalam memberikan bantuan nyata dan bentuk perhatian kepada individu. Work Life Balance merupakan upaya individu untuk menyeimbangkan antara pemenuhan kebutuhan perannya dalam kehidupan pekerjaan dan kehidupan pribadi. Dukungan yang diberikan oleh keluarga menjadi kunci sumber daya bagi seorang karyawan untuk bekerja (King, Mattimore, King, and Adams, 1995). Penelitian ini bertujuan untuk mengetahui gambaran dan pengaruh Family Support terhadap Work Life Balance pada Perawat di Rumah Sakit X. Hipotesis penelitian ini adalah Family Support memiliki pengaruh terhadap Work Life Balance pada perawat di Rumah Sakit X. Subjek penelitian ini berjumlah 55 perawat. Alat ukur Family Support menggunakan Family Support Inventory for Workers oleh King et al. (1995) dan alat ukur Work Life Balance berdasarkan teori Fisher. Analisis data menggunakan regresi berganda. Hasil penelitian menunjukkan 94,5% perawat mempunyai Family Support tinggi dan sebesar 96,4% perawat mempunyai Work Life Balance tinggi. Secara simultan, Family Support memberikan pengaruh sebesar 50,6% terhadap Work Life Balance. Aspek Family Support yang memberikan pengaruh paling besar terhap Work Life Balance adalah aspek Instrumental Asistance dengan pengaruh sebesar 25,71%, sedangkan aspek yang memberikan pengaruh paling rendah adalah Emotional Sustenance dengan pengaruh sebesar 24,89%.